The Influence of Training and Development on Employee Performance at CV Tiara Abadi pamekasan - Hamzah, Mohammad (Assyarikah: Journal of Islamic Economic Business, 2023)
One important factor in sustaining the company's existence in advancing quality and performance management is the mastery of capabilities possessed by human resources and the clarity of career development. A clean and healthy company is certainly due to good employee performance. Employee performance will improve if employees are given the training to improve their abilities and also a clear career development program. The purpose of this research is to find out the effect of training and career development to employeee performance at CV Tiara Abadi pamekasan, partially and Simultaneously. This research  is  classified  as  Explanatory  Research  with  a  quantitative  approach.  The sample used was 100 employee of CV Tiara Abadi pamekasan, with purposive sampling technique.  The  type  of  data  used  is  primary  data,  namely  data  collection  using  a questionnaire. Analysis of the data used is Multiple Linear Regression with SPSS. The results of this study indicate that training has a positive effect onemployee performance. And, career developmet has a Positive effect on employee performance.  Simultaneously training and career have positive and significant effect onemployee performance.